Childhood obesity - Skae, Mars (Henry Stewart Talks, 2016)
Childhood obesity: definitions, rates and global trends, Causes of childhood obesity, Co-morbidities in childhood obesity, Key determinants of obesity in childhood, Stigmatisation and psychological issues in the child, Obesity and the child with disability, Long term outlook for childhood obesity